Evaluating aerial landings in surfing: implications for performance and training (PhD Academy Award) - Forsyth, J. R. (British Journal of Sports Medicine, 2023)
Why did I do it? In surfing, aerial manoeuvres have become popular because they are associated with higher scores during surfing competitions.1 Although aerials can provide surfers with a competitive advantage, they are high-risk with low completion rates1 and have been linked to acute lower limb injuries2 due to the forces generated when landing. To increase success when performing aerials and mitigate these potentially injurious forces when landing, a better understanding of how aerials are executed, and which technique features are related to better landing performance, are required to inform effective training practices for surfers.